Frequency of Covert Urinary Retention in Women after Vaginal Birth of Baby: Postpartum Covert Urinary Retention - Zafar, Iqra; Syed, Sadaf Zahra; Waheed, Fatima; Zafar, Abeera; Sarwat, Asma; Parveen, Najma; Babi, Yasmin; Farhan, Eeshah (Pakistan Journal of Health Sciences, 2024)
Postpartum Covert Urinary Retention (PPUR) is a medical condition in which a woman’s spontaneous ability to micturate is present and the patient passes urine but the problem lies with the residual volume of urine as it was higher than normal. Sufficient data were lacking so this study will help us to determine the disease burden in our population to do better management. Objective: To determine the frequency of postpartum covert urinary retention in females after the birth of a baby through the vaginal route. Methods: It was a cross-sectional survey, conducted in Lady Willingdon Hospital, Lahore, from April 2019 to October 2019. A total of 383 patients fulfilling the inclusion and exclusion criteria were taken by non-probability consecutive sampling. As soon as the patients pass urine after the vaginal birth of the baby, a transabdominal ultrasound was planned to get an estimated value of postvoid residual urine volume. All gathered data were entered and analyzed using SPSS version 22.0. Results: The mean age was 30.14 ± 5.06 years. The mean gestational age was 39.58 ± 1.73 weeks. In 163 (42.6%) females, epidural analgesia was used, among 152 (39.7%) females, episiotomy was done and 225 (66.6%) females had prolonged duration of labor. In 200 (52.2%) females, had covert urinary retention while 183 (47.8%) did not. Conclusions: It was concluded that more than half i.e. 52.2% of the females had covert urinary retention. Hence appropriate attention must be ensured to nationally accepted definitions and management algorithms in the post-natal stage to reduce the burden of disease in our community.